Jump to content


Welcome to BrainDen.com - Brain Teasers Forum

Welcome to BrainDen.com - Brain Teasers Forum. Like most online communities you must register to post in our community, but don't worry this is a simple free process. To be a part of BrainDen Forums you may create a new account or sign in if you already have an account.
As a member you could start new topics, reply to others, subscribe to topics/forums to get automatic updates, get your own profile and make new friends.

Of course, you can also enjoy our collection of amazing optical illusions and cool math games.

If you like our site, you may support us by simply clicking Google "+1" or Facebook "Like" buttons at the top.
If you have a website, we would appreciate a little link to BrainDen.

Thanks and enjoy the Den :-)
Guest Message by DevFuse
 

Photo
- - - - -

Impossible math 4


  • Please log in to reply
2 replies to this topic

#1 comperr

comperr

    Advanced Member

  • Members
  • PipPipPip
  • 165 posts

Posted 09 July 2007 - 11:57 PM

1. a = b
2. a - b - 2 = a - b - 2
3. a(a - b - 2) = b(a - b - 2)
4. a2 - ab - 2a = ab - b2 - 2b
5. a2 - ab = ab - b2 - 2b + 2a
6. a2 - ab = ab + 2a - b2 - 2b
7. a(a - B) = a(b + 2) - b(b + 2)
8. a(a - B) = (a - B)(b + 2)
9. a = b + 2
10. b = b + 2
11. Thereforem 0 = 2

I have proven something similar with -10=any positive integer. I have since found this online and I am using the one I found and not my own.
  • 0

#2 Integral

Integral

    Newbie

  • Members
  • Pip
  • 5 posts

Posted 10 July 2007 - 06:25 AM

If a=b then a-b=0 and therefore the factor (a-B) can not be used to simplify or reduce.

Thanks
  • 0

#3 Integral

Integral

    Newbie

  • Members
  • Pip
  • 5 posts

Posted 10 July 2007 - 06:28 AM

Here's a similar one to yours:

x^2 - x^2= x^2 - x^2 => x(x-x)= (x-x)(x+x) => x=2x => 1=2

Thanks
  • 0




0 user(s) are reading this topic

0 members, 0 guests, 0 anonymous users